Análisis del impacto del bono de la vivienda en la calida de vida de las familias beneficiarias del sector urbano de la ciudad de Quito en el periodo 2007-2011 - Duche Tibán, Daniela Susana (2015)
In recent decades despite periods of economic instability in the country, the construction sector has had a considerable boom that has enabled the development of this sector, generating employment opportunities, financial economics streamlining the flow of money, and generates mobility in the environment. Considering the boom that has had the construction sector and the actions that the state determined in its governance; there is a need to study this branch of production, since its increase has informed largely by the delivery of the bonus of the housing by the State to the most vulnerable sectors of the population, that cannot access decent housing mainly by lack of financial resources. From this perspective, prepares an analysis of the impact of the bonus of the housing in the quality of life of the beneficiaries of the city of Quito period 2007-2011, which shows the impact on the variable income, housing, basic services, education, health, transport, environmental green areas, entertainment centers, shopping centers. The study allows us to see more thoroughly through the implementation of direct research conducted through a survey and considered better positive impacts that have improved the quality of life of the beneficiaries of the bond by more than 60% are satisfied to be in a better environment to perform their daily activities and the homeownership to live with dignity. Through the housing bond the State tries to reduce the housing deficit that exists and also to encourage change in the productive matrix to make developers more involved in social housing.